2020
DOI: 10.1055/a-1071-8028
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Liver Injury (DILI) in Patients with Depression Treated with Antidepressants: A Retrospective Multicenter Study

Abstract: Introduction Drug-induced liver injury (DILI) is the 4th most common cause of liver damage in Western countries and can be caused by antidepressants. Methods Against the background of increasing antidepressant prescriptions and increasing use of polypharmacy, we analyzed administered antidepressants and other pharmacological substances, liver toxicity, comorbid somatic secondary diseases together with the occurrence of DILI in a patient population of 6 centers throughout Germany. Results The majority of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 104 A multicenter retrospective analysis of 329 patients undergoing antidepressant therapy at 6 medical centers in Germany revealed that 5.1% of patients experienced increased serum transaminase levels during treatment, with 3 cases (0.9%) meeting the criteria for definite drug-induced liver injury (ALT level >5 times the upper limit of normal); furthermore, the study indicated that among the cases with a transaminase increase, the most commonly implicated antidepressants were mirtazapine, agomelatine, trazodone, and venlafaxine. 105 …”
Section: Common Liver Injury–causing Drugs Linked To Gut Microbiotamentioning
confidence: 99%
“… 104 A multicenter retrospective analysis of 329 patients undergoing antidepressant therapy at 6 medical centers in Germany revealed that 5.1% of patients experienced increased serum transaminase levels during treatment, with 3 cases (0.9%) meeting the criteria for definite drug-induced liver injury (ALT level >5 times the upper limit of normal); furthermore, the study indicated that among the cases with a transaminase increase, the most commonly implicated antidepressants were mirtazapine, agomelatine, trazodone, and venlafaxine. 105 …”
Section: Common Liver Injury–causing Drugs Linked To Gut Microbiotamentioning
confidence: 99%
“…Therefore, understanding DILI associated with antidepressants and safety monitoring is essential to optimize antidepressant treatment outcomes. Previous reports were based on retrospective multicenter studies, 12 , 13 case reports, 14 17 or case series. 18 To the best of our knowledge, there has been no comprehensive evaluation of the association between individual antidepressant drugs and DILI.…”
Section: Introductionmentioning
confidence: 99%
“…When depression and NAFLD are associated, there is an increased likelihood of complications and mortality [ 15 ]. With depression increasing, by up to 50%, the risk of NAFLD [ 16 ] and the antidepressant (AD) treatment often inducing liver injury (DILI) [ 17 , 18 , 19 , 20 ], the need for monitoring the liver function in depressed patients becomes apparent [ 21 , 22 ]. While an elevated value of alanine aminotransferase (ALT) serves as a reliable indicator of hepatocellular damage resulting from NAFLD, especially in males [ 23 ], and the hepatic toxicity induced by ADs [ 24 ], gamma-glutamyl transferase (GGT) levels typically rise in response to excessive alcohol consumption, making it a valuable biomarker for assessing alcohol-related liver damage and monitoring alcohol intake in clinical settings [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%